THE ANALYSIS OF PUBLIC NEEDS FOR RAIL TRANSPORT IN KRUENG GEUKUEH, ACEH, INDONESIA - Murni Hestika; Murtala Murtala (Journal of Malikussaleh Public Economics, 2020)
This study aims to analyze the level of public demand for railroad transportation in Krueng Geukuh, Dewantara District, North Aceh Regency. The survey method used is the dynamic survey method and static survey, the data analysis method used is using the Load Factor method. The results showed that the travel speed using the Train was 5.3 minutes from each station. The time between the train distance and other public vehicles is 60 minutes. Travel time required in 1 km is 1.88 minutes. Keywords: Load Factor, Travel Speed, Headway, Travel Time, Frequency, Wakru Wait